Effects of diet and antihyperglycemic drugs on erectile dysfunction: A systematic review. (13th May 2022) - Defeudis, Giuseppe; Mazzilli, Rossella; Di Tommaso, Alfonso Maria; Zamponi, Virginia; Carlomagno, Francesco; Tuccinardi, Dario; Watanabe, Mikiko; Faggiano, Antongiulio; Gianfrilli, Daniele
Abstract: Background: Erectile dysfunction is recognized as one of the complications of diabetes mellitus. To date, a wide gap of knowledge is present on the efficacy of pharmacological treatments of diabetes mellitus on erectile function, acting not only through metabolic control. Similarly, the effects of different diet regimens on erectile dysfunction are still debated. Objectives: We aimed to explore the effects of diet and antihyperglycemic drugs, considering both old and novel therapeutic approaches, on erectile function. Materials/methods: We performed a systematic review, following the PRISMA guidelines. The research was conducted on studies reporting erectile dysfunction assessment in subjects with diabetes and the relationship with diet and antihyperglycemic drugs. Results: The Mediterranean diet was effective in most studies for the protection of erectile function. Furthermore, antihyperglycemic drugs seem to show an overall protective role on erectile function. Discussion/conclusion: Although encouraging results are present for all classes of antihyperglycemic drugs, several studies are needed in humans, mainly on acarbose, pioglitazone, dipeptidyl‐peptidase‐4 inhibitors, and sodium‐glucose cotransporter‐2 inhibitors.